ANALISIS KINERJA DENGAN METODE BALANCED SCORECARD PADA RSUD.S.K.LERIK KOTA KUPANG - Herny Ellen Djunina; Wehelmina M. Ndoen; Christien C. Foenay (Journal of Management Small and Medium Enterprises (SMEs), 2017)
This research aim to know the performance of RSUD S. K. Lerik Kota Kupang that measured byBalanced Scorecard approaching. The research method is case study, with analytical techniquereferring to Balanced Scorecard approaching, those are Financial Perspective, Customer Perspective,Internal Business Process Perspective and Learning And Growth Perspective. The results of theanalysis show that Financial Perspective as measured by the Economic Ratio is categorized as"Very Economical", the Efficiency Ratio is categorized as "Not Efficient" and the EffectivenessRatio is categorized as "Very Effective". The Customer Perspective for Patient Satisfaction isincluded in the "Good" category and Customer Acquisition is in the "Good" category. For InternalBusiness Process Perspective, IGD building and bedding improvement (BOR) is categorized as"Good Enough" and TOI is also categorized as "Good". For Learning And Growth Perspective,Employee Satisfaction level is in the "Good" category, and for Productivity, employees of RSUD S.K. Lerik Kota Kupang had not maximized in revenue increasing. Thus, RSUD S. K. Lerik KotaKupang should pay attention to each perspective to improve its performanceKeywords : Performance, Balanced Scorecard